E-Nose and HS-SPME-GC-MS unveiling the scent signature of Ligusticum chuanxiong and its medicinal relatives - Xu, Wanjing; Zhang, Chao; Xu, Rong; Yang, Juan; Kong, Yijuan; Liu, Li; Tao, Shan; Wu, Yu; Liao, Hailang; Mao, Changqing; Xu, Zhengjun; Peng, Fang (Frontiers in Plant Science, 2025)
IntroductionTo explore the origin and evolution of Ligusticum Chuanxiong, we conducted a component analysis of Ligusticum Chuanxiong and its medicinal relatives.MethodsThis study encompassed seven species from various origins, including Chuanxiong (Ligusticum chuanxiong Hort.), Gansu Chuanxiong (Ligusticum chuanxiong cv. Gansu), Yunnan Chuanxiong (Ligusticum chuanxiong cv. Yunnan), Japanese Chuanxiong (Cnidium officinale Makino), Fuxiong (Ligusticum sinense ‘Fuxiong’), Gaoben (Ligusticum sinense), and Liaogaoben (Ligusticum jeholense), comprising 27 distinct materials. We employed headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) to identify various odor profiles from these species using electronic nose technology (E-nose). The method effectively identified volatile constituents in the leaves of these seven species.ResultsResults indicated that odor differences between L. chuanxiong and its medicinal relatives were predominantly observed in sensors W1W and W1S. Linear discriminant factor analysis (LDA) successfully distinguished five of the relatives; however, L. chuanxiong and L. sinense exhibited high odor similarity, limiting complete differentiation in some samples. HS-SPME-GC-MS identified a total of 118 volatile constituents, with eight differential volatiles identified: trans-Neocnidilide, β-Caryophyllene, β-Selinene, 5-Pentylcyclohexa-1,3-diene, (E)-Ligustilide, Butylphthalide, Neophytadiene, and Senkyunolide. Hierarchical cluster analysis (HCA) grouped L. chuanxiong, L. sinense, L. jeholense, and L. chuanxiong cv. Gansu together, highlighting the close relationship between L. chuanxiong and L. sinense. Joint analysis revealed a significant positive correlation between sensor W1W and the differential volatile component β-Caryophyllene, suggesting its potential for distinguishing closely related species.DiscussionThis study provides a foundational understanding of volatile components in the leaves of L. chuanxiong and its medicinal relatives using E-nose combined with HS-SPME-GC-MS, contributing to the discussion on their interspecific odor characteristics and relationships.